HUBUNGAN ANTARA KOMITMEN KEPEMIMPINAN DAN BUDAYA ORGANISASI DENGAN KINERJA GURU DI SMP NEGERI SEKECAMATAN PUTRI HIJAU - Kasidi Kasidi Kasidi (UNIVERSITAS BENGKULU, 2016)
The aim of the research is to find out the correlation between leadership commitment’s and cultural organization with teacher’s performance.The population of this research was 116teachers of junior high school of Putri hijau. The Sample was 54 respondents by using the randomg sampling technique. The method of this research used survey metthod. The datacollecting technique used questionance and documentation. The data were analized by using regression technique. The research produces three main conclusions, namely, 1) there is positiveand significant correlation between leadership commitment with teacher’s performance, 2) there is positive and significant correlation between cultural organization with teacher’s performance, 3) there is positive and significant correlation between leadership commitment and cultural organization simultaneously with teacher performance. The research concludes that teacher’s performance of state junior high school district Putri hijau north Bengkulu was enfluenced by leadership commitment’s and cultural organization.Keywords: leadership commitment, organizational culture, performance of teachers